Effect of Rifampin on the Immune Response in Guinea Pigs - Dajani, Basem M. (1973)
The effect of an oral dose of 20 mg of rifampin per kg per day on the immune response to killed Mycobacterium bovis var. BCG, 1-chloro-2,4-dinitrobenzene (DNCB), and sheep red blood cells (SRBC) was studied in adult female guinea pigs. Fully established cutaneous reactions to BCG or DNCB were markedly reduced during rifampin treatment but reverted to pretreatment levels after the drug was discontinued. When treatment was begun 7 days after immunization, positive reactions did not occur during drug administration but developed after cessation. When treatment was initiated 7 days before immunization, the response to these agents was completely suppressed during but also after rifampin was discontinued, suggesting that recognition and processing of the immunogens had been impaired. Rifampin had no effect on the secondary response to SRBC. When treatment was initiated either 7 days before or 2, 3, or 4 days after SRBC immunization, the primary response was abolished, but the reaction to a booster after drug withdrawal varied: some animals developed a normal secondary hemagglutinin response, but the majority reacted as if they had not been previously immunized. These studies indicate that rifampin is an active immunosuppressive agent in the guinea pig.